Guidance And Counseling Programs For Inclusive Education In Primary School - Pautina, Amalia Rizki; Pratiwi, Wiwik; Taligansing, Sri Yunita (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2019)
Inclusive education is a form of education service which does not distinguish between regular students and those with special needs, whether physical, social, intellectual, emotional, linguistic and so on. It also includes students in remote or backward areas, isolated indigenous communities, and experiencing natural disasters, social disasters, and economically incapable of having education in regular schools from primary school till senior high school. In primary schools providing inclusive education, schools are required to make adjustments both in terms of curriculum, educational facilities, and infrastructure, as well as learning systems so that it suits the individual needs of students. Besides, to maximize the implementation of inclusive education in primary schools, guidance, and counseling programs oriented to each individual are needed. This study uses a qualitative approach to the literature review method. The result of this research is guidance and counseling program at inclusive schools is directed at developing personality and life skills so that students can participate in the community and not become a burden on the family or community. The implementation of guidance and counseling programs in primary schools implementing inclusive education is carried out in four stages: planning, designing, implementing and evaluating.